SOLID POLYMER ELECTROLYTE FROM PHOSPHORYLATED CHITOSAN - FAUZI (NIM : 10508083), IQBAL
The need for secondary batteries is increasing every year. The secondary battery using a liquid electrolyte has some weakness. Solid polymer electrolyte is the alternative electrolytes are developed to replace the liquid electrolyte type. The study is conducted to determine the effect of phosphatation on the polymer electrolyte membrane of lithium perchlorate salts and chitosan. To determine the effect of the composition of each component on the properties of the polymer electrolyte, was carried out the characterization through the analysis of functional groups by FTIR (Fourier Transform Infrared), ion conductivity by EIS (Electrochemical Impedance Spectroscopy), thermal property by TGA (Thermogravimetric Analysis), and analysis mechanical properties by Tensile tester. The polymer electrolyte membrane of chitosan and lithium perchlorate was phosphated by using microwave for 60 seconds. The degree of deacetylation of chitosan derived from shrimp shells was obtained about 75,4 %. Relative molecular mass of chitosan obtained by the method viskometri is 796.792 g/mol. Phosphatation and the addition of lithium perchlorate salt can increase the conductivity of the membrane. Chitosan membrane conductivity increases from 6.33x10-6 S/cm to 5,54x10-4 S/cm after phosphatation, the maximum conductivity of chitosan membranes after adding lithium perchlorate of 15 % is 6,01x10-4 S/cm. The polymer electrolyte membrane of chitosan and perchlorate 15%, then phosphated by immersion in phosphoric acid, and radiated with microwave for two hours has ion conductivity of 1,37x10-3 S/cm, the mechanical resistance of 40,2 MPa, and a better thermal resistance. This polymer electrolyte membrane is potentially used for polymer electrolyte in lithium battery applications.